SIKAP MASYARAKAT SEKITAR KAWASAN MARUNDA TERHADAP RESTORASI EKOLOGI HUTAN MANGROVE DI KELURAHAN MARUNDA, KECAMATAN CILINCING, JAKARTA UTARA - Nesmi Puspitasari; Eny Lestari; Emi Widiyanti (Universitas Sebelas Maret, 2017)
This research aims to determine the factors that shape the attitudes of the community, to know the attitude of the community, to analyze the relationship between the factors that shape the public attitudes, and to analyze the differences of people's attitudes toward the economic impacts of the people who live close to the restoration site with the people who live far from Location of restoration of ecological restoration of mangrove forest. The location of the study was determined purposively. The sampling method used is proportional random sampling, with sample number 60 Marunda Pulo community. The result of the research shows that: (1) There is a significant relationship between the attitude of the community with the influence of others who are considered important. While there is a non-significant relationship between the attitude of the community towards age, type of work, formal education, non-formal education, and mass media exposure. (2) There is a significant difference between the attitude of the people whose location is 400 meters away from the coast with the attitude of the people whose residence is more than 400 meters from the beach.